1986
DOI: 10.1111/j.1526-4610.1986.hed2605243.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Diet in the Fasting Migraineur

Abstract: SYNOPSIS In migraine, are there different metabolic responses to glucose ingestion, and if so, do the patients have different detectable characteristics which may be of use to determine their treatment? Thirty two volunteer migraineurs, for whom fasting was a known precipitant, were challenged with a glucose meal after an overnight fast. Symptoms and glucose levels were recorded at intervals over three hours. Examination of the changes in symptoms, elicited two groups with opposite responses, which were also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The correlation between migraine and abnormal glucose metabolism is supported by a variety of evidence. Acorrelation was found between migraine and diabetes, 4 the most frequent triggering factor reported by migraineurs is fasting, and migraine is more likely in susceptible persons when there is low insulin receptor activation 5,6 . Insulin resistance was also suggested by Rainero et al, 19 who found higher glucose but similar insulin levels 180 minutes after OGTT in migraineurs than controls.…”
Section: Commentsmentioning
confidence: 87%
“…The correlation between migraine and abnormal glucose metabolism is supported by a variety of evidence. Acorrelation was found between migraine and diabetes, 4 the most frequent triggering factor reported by migraineurs is fasting, and migraine is more likely in susceptible persons when there is low insulin receptor activation 5,6 . Insulin resistance was also suggested by Rainero et al, 19 who found higher glucose but similar insulin levels 180 minutes after OGTT in migraineurs than controls.…”
Section: Commentsmentioning
confidence: 87%
“…The relationship between migraine and diabetes is still unclear, and there are conflicting results about migraine prevalence in patients with diabetes . Some studies supposed that migraine is more common in susceptible people in a condition of low insulin receptor activation . Rainero et al .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between migraine and diabetes is still unclear, and there are conflicting results about migraine prevalence in patients with diabetes [29]. Some studies supposed that migraine is more common in susceptible people in a condition of low insulin receptor activation [10,30]. Rainero et al suggested IR in patients with migraine, finding a higher glucose level and a similar insulin level in migraineurs compared with controls, 180 min after the OGTT [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the most common trigger was noise (95.6%) followed by stress (94.8%), sun exposure (89.6%) and fasting (74.1%). Fasting results in activation of insulin receptors which may trigger a migraine attack [28]. Low sucrose diets may reduce the frequency of migraine attack [29].…”
Section: Discussionmentioning
confidence: 99%